Mr S.H.: Perlindungan Hukum Negara Republik Indonesia bagi Kehidupan Layak Pengungsi Rohingya - Yurisdichristiawan, Deogoza; Lukman Hakim; Zulkarnain (Faculty of Law, University of Muhammadiyaha Surabaya, 2025)
Legal protection provided by the Republic of Indonesia to Rohingya refugees aims to ensure a decent standard of living despite Indonesia not being a party to the 1951 Refugee Convention and its 1967 Protocol. The study applies a normative juridical method by examining national legislation, Philipus M. Hadjon’s theory of legal protection, and international refugee law principles, particularly Non-Refoulement and Non-Discrimination. Findings indicate that legal protection remains confined to Presidential Regulation No. 125 of 2016, which regulates the discovery, sheltering, security measures, and immigration supervision of refugees. However, the absence of specific regulations establishing minimum standards for temporary accommodation results in suboptimal preventive and repressive protection by the government. The study concludes that clear and comprehensive regulations on temporary accommodation standards are required as part of the state’s responsibility to ensure adequate legal protection for Rohingya refugees within its jurisdiction.